Applying a big data analysis to evaluate the suitability of shelter locations for the evacuation of residents in case of radiological emergencies - Jin Sik Choi; Jae Wook Kim; Han Young Joo; Joo Hyun Moon (Nuclear Engineering and Technology, 2023)
During a nuclear power plant (NPP) accident, radioactive material may be released into the surrounding environment in the form of a radioactive plume. The behavior of the radioactive plume is influenced by meteorological factors such as wind direction and speed. If the residents are evacuated to a shelter in the direction of the flow of the radioactive plume, the radiation exposure of the residents may increase, contrary to the purpose of the evacuation. To avoid such an undesirable outcome, this paper applies a big data analysis to evaluate the suitability of the shelter locations near 5 NPPs in the Republic of Korea in terms of the seasonal wind direction frequency in those areas. To this end, the wind data measured around the NPPs from 2016 to 2020 were analyzed to derive the seasonal wind direction frequency using a big data analysis. These analyses results were then used to determine how many shelters around NPPs locate in areas with prevailing wind direction per season. Then, suggestions were made on the direction for residents not to evacuate, if possible, that is, the prevailing seasonal wind directions for 5 NPPs, depending on the season in which the accident occurs.